Latin America and refugee protection : regimes, logics, and challenges - Jubilut, Liliana Lyra; Vera Espinoza, Marcia; Mezzanotti, Gabriela, 1974- (Studies in forced migration, 2021)
"Looking at refugee protection in Latin America, this landmark edited collection assesses what the region has achieved in recent years. It analyses Latin America's main documents in refugee protection, evaluates the particular aspects of different regimes, and reviews their emergence, development and effect, to develop understanding of refugee protection in the region. Drawing from multidisciplinary texts from both leading academics and practitioners, this comprehensive, innovative and highly topical book adopts an analytical framework to understand and improve Latin America's protection of refugees"--